2022
DOI: 10.2196/39634
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ Perspectives on Telemental Health Usage After the COVID-19 Pandemic: Retrospective Analysis

Abstract: Background Mental health care pivoted to telemedicine during the COVID-19 pandemic, and there is uncertainty around the sustainability of this rapid shift. Objective This study examined how intentions to continue using telemedicine after the COVID-19 pandemic are influenced by provider perceptions of usefulness, ease of use, and professional social influence, facilitating organizational conditions. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…First, participants were recruited from the Doxy.me platform. While the demographics of Doxy.me users have been consistent with overall mental health care industry statistics ( American Psychological Association, 2022 ; Vogt et al, 2022 ; Wilczewski et al, 2022 ), future studies should aim to recruit from larger participant pools, ideally from across a variety of telehealth platforms. Second, most therapists in this study had used VR in casual settings, but none had used VR clinically.…”
Section: Discussionmentioning
confidence: 95%
“…First, participants were recruited from the Doxy.me platform. While the demographics of Doxy.me users have been consistent with overall mental health care industry statistics ( American Psychological Association, 2022 ; Vogt et al, 2022 ; Wilczewski et al, 2022 ), future studies should aim to recruit from larger participant pools, ideally from across a variety of telehealth platforms. Second, most therapists in this study had used VR in casual settings, but none had used VR clinically.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that a majority of mental health practitioners reported at least one practice adjustment during the PHE, such as providing additional therapeutic services [ 22 ] and that both the process and content of therapy often changed [ 23 ]. Changes in the service type likely resulted from a mix of other factors, including patient availability and preferences, changed provider preferences, and changed provider schedules or demands during the pandemic [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant portion expressed commitment to ongoing telemedicine utilization, indicating a potential long-term trend. Enhanced intention correlated with factors like social influence, perceived usefulness, telemedicine caseload, ease of use perception, and facilitating conditions (Wilczewski et al, 2022).…”
Section: Digital Healthcare Solutions and Chronic Diseases: Evidence ...mentioning
confidence: 97%